Identification and Validation of Potential Candidate Genes of Colorectal Cancer in Response to Fusobacterium nucleatum Infection - Zhang, Jiangguo; Wang, Zhimo; Lv, Hong; Li, Guojun (Frontiers in Genetics, 2021)
Objective: Recent investigations revealed the relationship between fusobacterium nucleatum (Fn) infection and colorectal cancer (CRC). However, how the host genes changes contribute to CRC in response to Fn infection remains largely unknown. Materials and methods: In the present study, we aimed to comprehensively analyze microarray data obtained from a Caco-2 infection cell model using integrated bioinformatics analysis and further identify and validate potential candidate genes in Fn-infected Caco-2 cells and CRC specimens. Results: We identified 10 hub genes potentially involved in Fn induced tumor initiation and progression. Furthermore, we demonstrated that the expression of centrosomal protein of 55 kDa (CEP55) is significantly higher in Fn-infected Caco-2 cells. Knocking down of CEP55 could arrest the cell cycle progression and induce apoptosis in Fn-infected Caco-2 cells. The expression of CEP55 was positively correlated with the Fn amount in Fn-infected CRC patients, and these patients with high CEP55 expression had an obviously poorer differentiation, worse metastasis and decreased cumulative survival rate. Conclusion: CEP55 plays an important role in Fn-infected colon cancer cell growth and cell cycle progression and could be used as a new diagnostic and prognostic biomarker for Fn-infected CRC.